Comparison of trauma‐dosed tranexamic acid versus aminocaproic acid in cardiac surgery in the setting of drug shortage. Issue 10 (23rd July 2022) - Dannemiller, Robert E.; Knowles, Danielle M.; Cook, Bryan M.; Goodberlet, Melanie Z.; Kelly, Julie M.; Malloy, Rhynn
Abstract: Background: Antifibrinolytic agents, tranexamic acid (TXA) and epsilon‐aminocaproic acid (EACA), are often used during cardiac surgery to decrease the number of allogenic blood transfusions and to prevent perioperative bleeding. Weight‐based TXA dosing regimens have been compared to fixed‐dose regimens of EACA with variable outcomes in perioperative blood product transfusions and chest tube output. Serious adverse events, including seizures, have been reported with higher doses of TXA. Fixed‐dose TXA regimens have been evaluated in trauma and orthopedic surgery but there is a paucity of evidence in the cardiac surgery population. Aims of the Study: To compare the safety and efficacy of fixed‐dose TXA versus EACA in patients undergoing cardiac surgery. Methods: A single‐center, retrospective chart review was conducted at a 793‐bed tertiary care academic teaching hospital comparing cardiac surgery patients receiving either fixed‐dose TXA 1000 mg followed by a 500–1000 mg infusion or EACA—7.5 g intravenous boluses followed by a 1–1.25 g/h infusion for the duration of the surgery. The major endpoint included chest tube output at 12 h, 24 h, and 7 days postoperatively. Minor endpoints included quantity and incidence of blood product transfusions and reported safety events. Results: There were 1544 patients included. Chest tube output was similar between groups and the TXA group required more intraoperative blood product transfusions (22.7% vs. 18.2%, p  = .03). There were no differences in the median quantity of total blood products administered postoperatively at 24 h or at 7 days. Reported safety events were similar between groups. Conclusion: Both fixed‐dose TXA and EACA may be considered safe and effective options for antifibrinolytic therapy in cardiac surgery patients.